ANALISIS POHON PENGHASIL BUAH-BUAHAN HUTAN YANG TERDAPAT DI HUTAN ALAM KANTUK KECAMATAN SEPAUK KABUPATEN SINTANG - Mariana, Nita; Dewantara, Iswan; Mariani, Yeni (Universitas Tanjungpura, 2013)
Plants producing forest fruits is one of the natural resources that has an important role of forest communities the suply, including the kind of fruit that has been used by people around the forest for food and other necessities . This study aims is to determine the diversity of fruits -producing trees that can be consumed by the forest around the District Nature Forest Kantuk Sub District Sepauk District Sintang . The method used is the method of combination of method and line method checkered path. 4 lines of observation , length 500 m , width of lanes and 20 x 20 m , 200 m spacing between lines . Observation plots measuring 10 x 10 m for poles and 20 x 20 m for tree level . The results found that the overall number of poles 57 vegetation types and levels of 58 types of trees . Fruit -producing trees for poles 21 forest types and levels of 19 species of trees The highest of Important Value Index (IVI) of overall vegetation at level poles and tree is derived from Purang (Macaraga sp) and Perepat (Sonneratia alba JB Sn) respectively are 28.7218%; 45.8161%. While the highest of Important Value Indeks (IVI) for Fruits producing free at poles and tree is derived from Tengkawang (Shorea sp) that are 69.5018; 100.9681%. and for fruit tree in poles and tree level are 0.8987 and 0.8464. Keywords : Trees , Fruits , Natural Forests , Important Value Index, species diversity